Enhanced nitrogen removal from low COD/TIN mainstream wastewater in a continuous plug-flow reactor via partial nitrification, simultaneous anammox and endogenous denitrification (PN-SAED) process. (February 2022) - Feng, Yan; Wang, Bo; Peng, Yongzhen; Li, Xiyao; Zhang, Qiong
Graphical abstract: Highlights: NAR maintained at above 95% under the normal operation even temperature <15℃. Ca. Brocadia was enriched in anoxic-carrier biofilms (6.67%) without inoculation. High NRE of 95.1% was obtained from low COD/TIN (3.4) municipal wastewater. Spontaneous anammox occurred in anoxic zone contributed to 13.5%±5.8% TIN removal. Abstract: A continuous plug-flow reactor with anaerobic/front-aerobic/anoxic/post-aerobic zones, where partial nitrification occurred in the front-aerobic zone, followed by simultaneous anammox and endogenous denitrification in the anoxic zone (PN-SAED), was built up to treat municipal wastewater. Alternating anoxic/aerobic conditions and longer anoxic duration facilitated stable partial nitrification. The nitrite accumulation ratio (NAR) was maintained at 97.4 ± 1.2%, with temperatures between 13.3℃ to 19.8℃. Candidatus Brocadia were naturally enriched in-situ from the anoxic zone with relative abundances of 31.93% and 6.67% on the agitator blade and carriers, respectively. High removal efficiencies of total inorganic nitrogen (TIN) (95.1 ± 1.9%) and effluent TIN (2.6 ± 1.1 mg N/L) were acquired from low COD/TIN (3.4 ± 0.4) municipal wastewater with anammox contribution of 13.5%±5.8% to TIN removal. The PN-SAED process is a promising mainstream nitrogen removal method.